Perturbation-Iteration Method for Solving Differential-Difference Equations Having Boundary Layer - Singh, Raghvendra Pratap; Reddy, Y. N. (Communications in Mathematics and Applications, 2020)
In this paper, a perturbation iteration method is described for solving differential-difference equations having boundary layer. Firstly, the given differential-difference equation having boundary layer is converted into a singularly perturbed ordinary differential equation using Taylor's transformation. Then perturbation iteration method applied to solve the resulting singularly perturbed ordinary differential equation. To demonstrate the applicability of this method, three model examples are solved. It is observed that the perturbation iteration method produces very good approximation to the exact solution.
Keywords: Differential-difference equations; Boundary layer; Perturbation iteration method